Hydroxypropyl methylcellulose mediated precipitation inhibition of sirolimus: from a screening campaign to a proof-of-concept human study - Petruševska, Marija; Homar, Miha; Petek, Boštjan; Resman, Aleksander; Kocjan, Darko; Urleb, Uroš; Peternel, Luka (American Chemical Society (ACS), 2013)
The aim of this study was to develop a sirolimus (BCS class II drug substance) solid oral dosage form containing a precipitation inhibitor, which would result in an improved sirolimus absorption in humans compared to the formulation containing nanosized sirolimus without a precipitation inhibitor, i.e., Rapamune. The selection of the precipitation inhibitor was based on the results of a screening campaign that identified two "hit" excipients: HPMC 603 (i.e., Pharmacoat 603) and Poloxamer 407. However, in a confirmatory precipitation inhibitor study using biorelevant media (Fa/FeSSIF) HPMC 603 more effectively inhibited sirolimus precipitation than Poloxamer 407. In the PAMPA assay, HPMC 603, but not Poloxamer 407, significantly increased the flux of the sirolimus across the membrane lipid layer. Additionally, a differential scanning calorimetry (DSC) and an infrared (IR) spectroscopy study revealed that interactions between the sirolimus and HPMC 603 were developed that could lead to the observed precipitation inhibition effect. Based on the above data, two formulations with HPMC 603-coated sirolimus particles were developed, namely, formulation A (d (0.5) = 0.21 μm) and formulation B (d (0.5) = 1.7 μm). A human pharmacokinetic study outlined that significantly higher AUC and Cmax were obtained for formulations A and B in comparison to Rapamune. This result could be attributed to the HPMC 603 (Pharmacoat 603) mediated sirolimus precipitation inhibition resulting in improved sirolimus absorption from the gastrointestinal tract in humans.